Increase of Micro-vessels Beneath the Pleural Surface on CT Predicts Pleural Adhesions - Kawamura, Tomoyuki; Kobayashi, Naohiro; Goto, Yukinobu; Sato, Yukio (The Thoracic and Cardiovascular Surgeon, 2022)
Background Pleural adhesions are often troublesome in lung surgeries. In some dense pleural adhesions, blood vessels between lung and chest wall (BVLC) are found during surgery. Theoretically, BVLC would increase the amount of blood flow just below the visceral pleura and could allow blood vessels beneath the pleural surface to be clearly visualized on CT. In this study, we investigated whether it was possible to identify the typical CT findings of cases with BVLC.Methods Medical records and imaging findings of 186 patients who underwent surgery for lung tumors in our institution were retrospectively reviewed.Results BVLC was found in 56 patients, of whom 44 (79%) had findings on preoperative CT that indicated increase of micro-vessels just below pleura. In the 21 patients with BVLC of ≥1 mm vessel diameter, the same CT findings were recognized in 19 cases (90%).Conclusion Our results indicate that the CT finding of increased micro-vessels just below pleura has the potential to be used as a novel predictor of pleural adhesion.
Keywords: pleural adhesion; preoperative CT; thoracic surgery